Sistem Informasi Pariwisata Wilayah Danau Ranau Berbasis Website - Khotimah, Indah Husnul; Fatmasari, Fatmasari; Yulianingsih, Evi; Nasir, Muhammad (Program Studi Teknik Informatika Universitas Pamulang, 2023)
The lake Ranau is one of the tourist attractions for tourists, sometimes it is difficult to reach information via the web page. Web-based information systems are needed both for citizens and for tourists to know which tourist attraction is on their way. Lake Ranau Tours have recently become one of the most outstanding Tours in south Sumatra because of the annual national events held on lake Ranau. A few articles on these Tours on some local platforms, leaving some visitors with complete information on lake ranau Tours, hence a tourist information system is necessary for one of the tourist media to know information about tourist attractions, lodgings, tourism Tours, and some of the annual events on lake ranau Tours. In this research, Design Thinking is used as a system development method and UML (Unified Modelling Language) is used as a system design. Design Thinking methods help researchers to do systematic research, since structured methods make researchers easier. In addition to some of the features on this website such as fire maps, youtube videos on Tours, accommodating information, and so on will be helpful to tourists on lake Ranau.